PENGARUH ATRIBUT KUALITAS AUDIT TERHADAP KEPUASAN KLIEN (STUDI EMPIRIS PADA BRI KOTA KENDARI) - Khasanah, Azizul (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
The study aims to determine the effect of audit quality attributes on client satisfaction (Empirical study at BRI Kendari City), data collection was carried out using a questionnaire. Data obtained from 20 people. Data analysis using simple regression. The results of the analysis show that Audit Quality Attributes affect client satisfaction at BRI Kendari City. It can be indicated, that the increase in client satisfaction is good where the implementation of Audit Quality Attributes at BRI Kendari City is generally very good. The results showed that most responders strongly agree to perform Audit Quality Attributes at BRI Kendari City which in turn will increase client satisfaction at BRI Kendari City. This good client satisfaction at BRI Kendari City is inseparable from the Audit Quality Attributes carried out by BRI Kendari City. Because basically the implementation of Audit Quality Attributes is directed at strategic areas and is operationally focused on activities that can provide more meaningful input for Bank management in order to achieve the goals set in accordance with the vision and mission of the organisation.